2014
DOI: 10.1021/ic4029589
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite YCrO3/Al2O3: Characterization of the Core–Shell, Magnetic Properties, and Enhancement of Dielectric Properties

Abstract: Multifuncionality in polycrystalline multiferroic ceramics can be improved using an advanced synthesis process. In this work, core-shell design is being proposed to enhance the transport properties of biferroic YCrO3. The atomic layer deposition (ALD) thin-film growth technique was used for the YCrO3/Al2O3 (Y@Al) nanocomposite fabrication. A continuous, amorphous, and uniform Al2O3 shell, a few nanometers thick, was obtained and characterized by X-ray photoelectron spectroscopy, X-ray diffraction, and high-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…It was observed that the bulk sintered nanocomposite have similar features as those reported in Ref. . Thereby, henceforth and for simplicity, the nanocomposite pellets will be referred as pristine, 50, 500, and 1000 ALD‐cycles.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…It was observed that the bulk sintered nanocomposite have similar features as those reported in Ref. . Thereby, henceforth and for simplicity, the nanocomposite pellets will be referred as pristine, 50, 500, and 1000 ALD‐cycles.…”
Section: Resultssupporting
confidence: 64%
“…Each particle was coated with a nanometric layer of Al 2 O 3 using the atomic layer deposition (ALD) technique. The experimental procedure of the nanocomposite fabrication has been described in detail elsewhere . The microstructural characterization of the powders was performed using high‐resolution transmission electron microscopy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slight changes in the intensity of peak (111) and peak (200) were observed which present a clear dependence on the number of interface. It indicates that amorphous AO layers might have impacts on the growth of SDC near the interface possibly due to strong interfacial interactions between the oxides [35,37]. The average crystalline sizes of SDC were calculated using Scherrer's formula and plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy being a local probe can provide a better insight to enquire the local distortion compared with neutron or XRD. Whereas most of the above experiments suggest that YCO is a RT ferroelectric, there are no reports of a well saturated P‐E loop for this system . Therefore, it is indeed an intriguing question that even when the electrical leakage is low, why YCO is a poor ferroelectric at RT.…”
Section: Introductionmentioning
confidence: 99%